1999
DOI: 10.2165/00002018-199921010-00002
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Risks of Transfer from Oral Agents to Insulin in Type 2 Diabetes Mellitus

Abstract: The treatment of type 2 diabetes mellitus remains controversial. Since most patients are overweight or obese, regimens based on dietary modification and increased physical exercise are logical and safe treatment approaches. However, the long term impact of these interventions is frequently disappointing and pharmacotherapy is therefore required in the majority of patients. Oral antidiabetic agents, principally the sulphonylureas and biguanides, are often only partially effective, even in combination. Insulin i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 87 publications
0
15
0
Order By: Relevance
“…33 Furthermore, insulin therapy has limited long-term efficacy in type 2 diabetes because of poor patient compliance to the regimen complexity and fear of weight gain and reduced quality of life. 34 In addition, glycemic control tends to deteriorate over time even after treatment. 35 The results of the Costs of Diabetes in Europe-Type 2 indicated that most patients with type 2 diabetes have either poor or borderline glycemic control.…”
Section: Clinical Interest Of a Surgical Treatment Of Type 2 Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Furthermore, insulin therapy has limited long-term efficacy in type 2 diabetes because of poor patient compliance to the regimen complexity and fear of weight gain and reduced quality of life. 34 In addition, glycemic control tends to deteriorate over time even after treatment. 35 The results of the Costs of Diabetes in Europe-Type 2 indicated that most patients with type 2 diabetes have either poor or borderline glycemic control.…”
Section: Clinical Interest Of a Surgical Treatment Of Type 2 Diabetesmentioning
confidence: 99%
“…First, long-term glycemic control would not be impaired by a patient's lack of compliance as it happens for diets, exercise, or complex medical regimens. 34 Moreover, a surgical treatment of type 2 diabetes could decrease the overall economic burden on health care systems by avoiding the costs of a life-long medical therapy. Tight blood glucose control is indeed associated with increased cost of intensive medical management 39 and therefore surgery might be a cost-effective option for the management of type 2 diabetes.…”
Section: Clinical Interest Of a Surgical Treatment Of Type 2 Diabetesmentioning
confidence: 99%
“…So far, no pharmacological cure for type 2 diabetes exists, but recent findings suggesting long-term improvement in glucose homeostasis in obese patients who underwent bariatric surgery may provide new opportunities in the fight against this global disease. [1][2][3] Buchwald et al, 4 in a meta-analysis of 22,094 patients with type 2 diabetes, who underwent gastrointestinal bypass for morbid obesity, showed that greater than 80% had complete resolution of their diabetes postoperatively. In addition, all gastrointestinal bypass procedures, such as the Roux-en-Y gastric bypass (RYGB) and biliopancreatic diversion (BPD), demonstrate a great improvement in glucose tolerance, with reported rates of 83.7-98.9% having complete resolution of diabetes.…”
mentioning
confidence: 99%
“…50 The risks and benefits of insulin therapy in patients with type 2 diabetes has been a topic of much debate. 51 Concerns have been expressed that by inducing hyperinsulinemia, insulin therapy might be detrimental to vascular health. However, the effects of insulin on atherothrombosis have been clouded by studies that have sometimes had limited relevance for human pathophysiology 52 and that have failed to make the crucial distinction between hyperinsulinemia and deficient cellular insulin action.…”
Section: Hyperglycemiamentioning
confidence: 99%
“…The failure of insulin therapy to provide unequivocal evidence of protection against macrovascular disease in the UKPDS should not detract from more enthusiastic use of insulin. 51 There are sound theoretical reasons to favor insulin therapy in patients in whom insulin-or insulin action-is deficient. In addition to an adverse profile of metabolic risk factors, defective cellular insulin action may also have direct implications for the vasculature.…”
Section: Hyperglycemiamentioning
confidence: 99%